2001
DOI: 10.1034/j.1399-3038.2001.0129999107.x
|View full text |Cite
|
Sign up to set email alerts
|

A contiguous deletion syndrome of X‐linked agammaglobulinemia and sensorineural deafness

Abstract: Hearing loss in patients with X-linked agammaglobulinemia is often attributed to recurrent infections. However, recent genetic studies suggest a different etiology in some patients. We present three unrelated patients, 6, 9, and 14 years of age, with large deletions of the terminal portion of the Bruton tyrosine kinase (Btk) gene extending 4.2-19 kb beyond the 3' end of the gene. The DNA immediately downstream of the 3' end of Btk contains the deafness-dystonia protein gene (DDP). Mutations in this gene have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Therefore, the differential features of intact sensory structures of the inner ear and severely depopulated auditory neurons helped to document that this X-linked, recessive and syndromic hearing loss can be characterized as an AN. Work by Richter et al [2001] supports these aforementioned structural changes by showing audiometric data (normal tympanograms, intact OAEs, absent acoustic stapedius reflexes, and desynchronized ABRs) that localize the site of dysfunction to the auditory nerve. Moreover, the initial temporal bone findings reported by Merchant et al [2001] were subsequently confirmed and expanded upon in 4 additional cases [Bahmad et al, 2007].…”
Section: Mohr-tranebjaerg Syndromementioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, the differential features of intact sensory structures of the inner ear and severely depopulated auditory neurons helped to document that this X-linked, recessive and syndromic hearing loss can be characterized as an AN. Work by Richter et al [2001] supports these aforementioned structural changes by showing audiometric data (normal tympanograms, intact OAEs, absent acoustic stapedius reflexes, and desynchronized ABRs) that localize the site of dysfunction to the auditory nerve. Moreover, the initial temporal bone findings reported by Merchant et al [2001] were subsequently confirmed and expanded upon in 4 additional cases [Bahmad et al, 2007].…”
Section: Mohr-tranebjaerg Syndromementioning
confidence: 78%
“…The gene responsible for MTS maps to Xq22, which is adjacent to the gene causally linked to agammaglobulinemia [Jin et al, 1996] that also includes sensorineural hearing loss as part of its clinical phenotype [Richter et al, 2001]. Co-expression of TIMM8A and TIMM13 with the calcium-binding mitochondrial aspartate glutamate carrier protein (Aralar1) and prominent signals in largecaliber peripheral and CNS neurons indicate that insufficient malate-aspartate NADH shuttling combined with changes in Ca 2+ concentration in specific cell types might explain the pathological process in MTS [Roesch et al, 2002[Roesch et al, , 2004.…”
Section: Mohr-tranebjaerg Syndromementioning
confidence: 99%
“…[8][9][10] Of these, only three break point junctions have been cloned. 14,16 In this study, we describe three patients with 63, 150 and 196 kb large deletions at the Xq22 region, which included BTK and TIMM8A.…”
Section: Discussionmentioning
confidence: 99%
“…1 As BTK and TIMM8A are positioned in close genomic proximity, gross gene deletions can result in disruption of both genes causing a contiguous deletion syndrome of XLA and MTS, which has been observed previously in nine families. 4,[8][9][10] In this study, we describe three patients with gross deletions including the BTK and TIMM8A genes. We characterized the deletions and identified the genomic break points by combining comparative genomic hybridization (CGH) array, DNA fluorescence in situ hybridization (FISH) and long accurate (LA)-PCR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Contiguous deletion syndrome of XLA and sensorineural deafness has been reported in four subjects secondary to gross deletion of 3′ end of BTK and deletion of DDP1 gene (DDP1,OMIM #300356) located adjacent the 3′ end of BTK [17]. Mutations in DDP1 cause a rare X-linked neurodegenerative disease termed as Mohr-Tranebjaerg syndrome (MTS), which is characterized by progressive neurological deficits including early-onset of deafness [2].…”
mentioning
confidence: 99%